DEPOSIT INSURANCE – CONVENTIONAL AND SHARIAH APPROACH - Lekpek, Ahmedin (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Deposit insurance has become an integral element of the modern banking system, which contributes to the safeness of depositors and the business stability of banks. This paper analyzes the conventional and Shariah approach to deposit insurance. The aim of this paper is to consider the features of the conventional and Shariah approach to deposit insurance, as well as their similarities and differences. Based on the analysis of the mentioned approaches, it can be concluded that, according to their function in the banking system, the Islamic deposit insurance model, created in accordance with Shariah principles, and the conventional deposit insurance model do not differ significantly. The difference is primarily reflected in the fact that the conventional insurance model contains certain Shariah-prohibited elements, which come to the fore in financing the deposit insurance system and investing available surplus funds.